Silver-polymer nanocomposites: Structural, thermal and electromechanical elucidation for charge storage applications. (May 2020) - Nasar, Gulfam; Azhar Khan, Muhammad; Nadeem, Qaisar; Amin, Hazrat; Ahmad, Nisar; ur Rehman, Jalil; Khalil, Uzma; Saleem Khan, Muhammad
Graphical abstract: Highlights: Silver nanoparticles were prepared and were used to develop PVA/Ag nanocomposites. Electrical properties of the composites were enhanced to 10 −5 S cm −1 . PVA/Ag nanocomposites films exhibited improved mechanical properties and surface morphology. Abstract: PVP stabilized Silver nanoparticles were synthesized and were used to prepare different compositions of polymer nanocomposites using poly (vinyl alcohol) as a polymer matrix. AC impedance spectroscopy, tensile testing (tensile strength, Young's modulus, elongation at break), atomic force microscopy (AFM), X-Ray diffraction (XRD), Thermogravimetric analysis (TGA/DTA) and Scanning Electron Microscopy (SEM) were used to characterize the prepared nanocomposite samples. Through this communication, we are reporting a much-enhanced electrical conductivity and mechanical properties of the nanocomposite films. The AFM and SEM propose a smooth surface morphology with uniformly dispersed nanoparticles. A fairly controlled size and uniform morphology discloses that PVP has played its role in controlling the diameter and dispensability of the nanoparticles. The outcome of the XRD suggests a semi crystalline structure of XRD results suggest that the prepared nanocomposite exhibits the semi-crystalline nature. Thermal analysis depicts that the thermal stability enhances as a function of the silver nanoparticles.